The Correlation Between Reading Achievement and Writing Achievement to the Eight Graders of Bilingual Class At SMP Negeri 1 Palembang - Arif Pamuji (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
Abstract: The objective of this research was to find out whether or not there is a correlation between reading achievement and writing achievement. The sample of this research was taken by using purposive sampling with total 36 students of the bilingual class in eighth grade students of SMP Negeri 1 Palembang in the academic year 2007/2008. The data were obtained by using reading comprehension test and writing test. To verify the hypotheses, the primary data were analyzed by using correlation and regression analyses by means of Statistical Product and Service Solution (SPSS) version 12.00 computer program. Based on the data analysis, the correlation coefficient (rxy) was 0.614 at the significance level p< 0.05 in two tailed. Since the value of r-obtained was higher than the critical value of r-table (0.614 >0.3291), the null hypothesis (Ho) was rejected and consequently, the research hypothesis (H1) was accepted. This shows a significant correlation between the reading Achievement and the writing Achievement to the eighth graders of bilingual class at SMP Negeri 1 Palembang. Based on the regression analysis, it was found that students’ reading achievement determined or influenced 37.7 % of their writing achievement and the rest (62.3 %) was defined by other factors. It means that there was a significant influence of reading achievement on the students’ writing achievement. Key words: reading achievement and writing achievement